2015
DOI: 10.17221/8418-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors of dog aggression in the Slovak Republic

Abstract: Canine aggression is a widespread problem which receives a lot of attention from the media. It has important consequences in terms of public health and animal welfare. To address this issue it is necessary to first determine its epidemiological characteristics in the target population. This study was aimed at exploring the characteristics and determining the risk factors for dog aggression in the Slovak Republic and, in particular, for aggression directed at humans. For this purpose, we used a questionnaire di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
6
1
1
Order By: Relevance
“…They considered 177 dogs for the study of aggressive behavior. Out of it, nearly 50% of the dogs showed owner-directed aggression and the remaining showed aggression toward unfamiliar people [27]. Most male dogs and informal training dogs have more aggressive behavior [28].…”
Section: Resultsmentioning
confidence: 99%
“…They considered 177 dogs for the study of aggressive behavior. Out of it, nearly 50% of the dogs showed owner-directed aggression and the remaining showed aggression toward unfamiliar people [27]. Most male dogs and informal training dogs have more aggressive behavior [28].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was found that gonadectomy of trained male dogs caused them to become more aggressive than a trained female dog [ 37 ]. Matos et al [ 38 ] found that the castration of trained dogs caused them to show more aggressiveness toward trainers; especially, trained male dogs showed more aggressiveness toward trainers. On the other hand, intact trained male and female dogs were lower in showing aggression and biting during training than castrated trained dogs [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food aggression is rather common in the pet dog population, too. In the Slovak Republic, 6.2% of survey respondents indicated that their pet dog sometimes, usually, or always displayed aggressive behavior when disturbed while eating versus 11.9% when disturbed while chewing on a treat [9]. In the United States, between 10% [4] and 28.9% [3] of shelter dog adopters reported food aggression in the home after adoption (based on responses to follow-up surveys).…”
Section: Discussionmentioning
confidence: 99%